1997
DOI: 10.1128/mcb.17.5.2521
|View full text |Cite
|
Sign up to set email alerts
|

Heteromeric and Homomeric Interactions Correlate with Signaling Activity and Functional Cooperativity of Smad3 and Smad4/DPC4

Abstract: Homologs of Drosophila Mad function as downstream mediators of the receptors for transforming growth factor ␤ (TGF-␤)-related factors. Two homologs, the receptor-associated Smad3 and the tumor suppressor Smad4/DPC4, synergize to induce ligand-independent TGF-␤ activities and are essential mediators of the natural TGF-␤ response. We now show that Smad3 and Smad4 associate in homomeric and heteromeric interactions, as assessed by yeast two-hybrid and coimmunoprecipitation analyses. Heteromeric interactions are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
152
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(168 citation statements)
references
References 25 publications
16
152
0
Order By: Relevance
“…In addition, mutant forms of Smad2 or Smad3 with short deletions in their C termini were found not to interact with Smad4 in this assay (45,46). Our observation that C-terminal peptides of Smad2 bind GST-Smad4 is consistent with these data.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, mutant forms of Smad2 or Smad3 with short deletions in their C termini were found not to interact with Smad4 in this assay (45,46). Our observation that C-terminal peptides of Smad2 bind GST-Smad4 is consistent with these data.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies using the yeast two-hybrid interaction screen indicated that the C-terminal domains of Smad2 and Smad3 are important for the heteromeric interactions with Smad4 (45,46). In addition, mutant forms of Smad2 or Smad3 with short deletions in their C termini were found not to interact with Smad4 in this assay (45,46).…”
Section: Discussionmentioning
confidence: 81%
“…As shown in Figure 6a, TGF-b augmented the activity of GAL4-Smad3 by 7.0-fold. GAL4-Smad3C, which has only the MH2 domain, had stronger activity (16.7-fold) than the wild type, consistent with a previous report (Wu et al, 1997). However, mutation of K378 (GAL4-Smad3C(K378R)) and mutation of all four lysines (GAL4-Smad3C(4KR)) significantly decreased the transcriptional activity (85 and 97% reduction, respectively).…”
Section: Acetylation Regulates the Transcriptional Activity Of Smad3supporting
confidence: 90%
“…K378 is fully conserved among all Smads and among all members of this family in various species. The MH2 domain of the Smad proteins exhibits a transactivation function through heterologous fusion with the GAL4 DNA-binding domain (Wu et al, 1997). We therefore evaluated the effect of the Smad3 acetylation of Smad3 on its function as a transactivator (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…lA). It is known that overexpressed Smad2 and SmadS can partially bypass the requirement for ligand and localize in the nucleus, oligomerize, and activate downstream events (Wu et al 1997;Zhang et al 1997). Activation of TGF-p signaling can further enhance these events.…”
Section: Tgf-^-and Smads-induced Degradation Of Snon Is Mediated By Tmentioning
confidence: 99%